Iron-cobalt layered double-metal hydroxide modified kaolin adsorption material as well as preparation method and application thereof

Modified kaolin by hydrothermal method, using iron-cobalt layered bimetallic hydroxide and kaolin embedded combination to form a flower-like agglomerate structure, solving the problems of low removal rate and high preparation cost of existing adsorbent materials, and achieving high efficiency Adsorbent material that removes organic pollutants and maintains adsorption capacity.

CN119500060APending Publication Date: 2025-02-25LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411828259.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing problems of low removal rate, limited amount, complex preparation and high preparation cost.

Method used

The kaolin was modified by hydrothermal method, and the iron-cobalt layered bimetallic hydroxide was used to incorporate the kaolin into an embedded combination to form a loose flower-like agglomerate structure, which enhanced the number of adsorption sites and binding strength.

Benefits of technology

It significantly improves the adsorption performance of adsorbent materials, can efficiently remove organic pollutants such as ciprofloxacin, and maintains a high adsorption capacity through multiple microwave regeneration, reducing wastewater treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500060A_ABST
    Figure CN119500060A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-cobalt layered double-metal hydroxide modified kaolin adsorption material as well as a preparation method and application thereof. The iron-cobalt layered double-metal double hydroxide modified kaolin adsorption material is obtained by adopting a hydrothermal method. After modification, the pore structure and the surface property of the kaolin can be improved, and the adsorption capacity of the kaolin to organic pollutants is remarkably improved. The iron-cobalt layered double-metal double hydroxide modified kaolin adsorbing material adsorbing the organic pollutants can effectively recover the original adsorption capacity after being regenerated by microwaves, and can be recycled for more than 5 times. The adsorption material is simple to prepare, high in adsorption efficiency, stable, environment-friendly, safe and non-toxic to a human body, can be used for adsorbing organic pollutants in a water body, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental engineering, and in particular relates to an iron-cobalt layered double metal hydroxide modified kaolin adsorption material and a preparation method and application thereof. Background Art

[0002] In recent years, the global consumption of antibiotics has been increasing. Ciprofloxacin (CIP) is widely used in the treatment of human and animal diseases, and has the characteristics of non-biodegradability, high hydrophilicity, low volatility and relatively long half-life. Therefore, CIP is difficult to be fully utilized and metabolized. Those CIPs that cannot be completely decomposed are released into groundwater, surface water, soil, etc., seriously endangering the environment and threatening the health of humans and other organisms.

[0003] At present, the treatment methods used for antibiotics such as CIP at home and abroad mainly include electrochemical method, photocatalytic degradation method and adsorption method. Among them, adsorption method is considered to be the most effective and convenient technology for treating organic pollutants in water and wastewater due to its high efficiency, low cost, wide adaptability and environmental friendliness. Based on the adsorption method, it is crucial to find an efficient and effective adsorbent material. At present, it has been reported that kaolin shows potential in removing heavy metals from water. However, the adsorption capacity of natural kaolin is limited by its small specific surface area, underdeveloped pore structure, and few surface active sites, which limits its performance in practical applications. At present, there are many studies on the modification of kaolin using surfactants, metal ions and metal elements. In the present invention, kaolin is modified with double metal hydroxides. Since the double metal hydroxides are layered structures, they will be embedded and combined with kaolin to form a loose flower-like aggregate structure, which is conducive to the closer combination of Fe, Co, -OH and -C=O in the iron-cobalt double metal hydroxides with the -OH, -Si=O and -Al=O functional groups in kaolin, forming a stronger chemical bond, and enhancing the number and bonding strength of coordination bonds and hydrogen bonds. Modification of kaolin with iron-cobalt layered double metals will increase the chemical activity of the kaolin surface, effectively increase the number of its adsorption sites and its adsorption capacity, and there are few reports on the research on the treatment of organic wastewater. In addition, the adsorbent still has a good adsorption effect after five microwave regenerations. Summary of the invention

[0004] The present invention aims to provide a method for preparing an iron-cobalt layered double metal hydroxide modified kaolin adsorption material, thereby improving the adsorption performance of kaolin to solve the problems of low removal rate, limited quantity, complex preparation and high preparation cost of existing organic matter removal adsorption materials.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The chemical formula of an iron-cobalt layered double hydroxide modified kaolin adsorption material is [Co 0.67 Fe 0.33 (OH)2] 0.33 (CO3) 0.16 mH2O@Al2[(OH)4 / Si2O5], with an embedded flower-like structure and a specific surface area of ​​85-90m 2 / g, the total void volume is 0.2-0.3cm 2 / g.

[0007] The preparation method of the above-mentioned iron-cobalt layered double metal hydroxide modified kaolin adsorption material comprises the following steps:

[0008] 1) FeCl3·6H2O and CoCl2·6H2O were mixed according to Fe 3+ / Co 2+ The molar ratio is 1.0:2.0 and the total concentration is 1.0M. It is first dissolved in deionized water, mixed evenly, and then kaolin is added thereto at a solid-liquid ratio of 0.1g / 1mL. After mixing evenly, urea is added thereto, and the pH is maintained at 10.0;

[0009] 2) The obtained mixture is transferred to an autoclave lined with polytetrafluoroethylene, and hydrothermally treated at 160° C. under isothermal airtight conditions for 12 hours. After the reaction is completed and cooled to room temperature, the obtained sample is washed with deionized water until neutral, vacuum dried, fully ground, and stored in a sample bottle for later use, thereby obtaining an iron-cobalt layered double metal hydroxide loaded on a kaolin adsorption material.

[0010] The reactions involved in the preparation process are as follows:

[0011] CoCl2·6H2O+H2O→Co 2+ +2Cl - +7H2O

[0012] FeCl3·6H2O+H2O→Fe 3+ +3Cl - +7H2O

[0013] CO(NH2)2+3H2O→2NH 4+ +2OH - +CO2

[0014] CO 2+ +2OH - →CO3 2- +H2O

[0015] (1-x)Co 2+ +xFe 3+ +2OH - +CO32- +mH2O→[Co 2+ 1-x Fe 3+ x (OH)2] + x( CO3 2- ) x / 2 mH2O

[0016] The application of the above-mentioned iron-cobalt layered double metal hydroxide modified kaolin adsorption material in removing organic pollutants in wastewater.

[0017] Furthermore, the above application is specifically performed as follows: adding iron-cobalt layered double hydroxide modified kaolin adsorption material to wastewater containing 20 mg / L organic pollutants, placing it on a magnetic stirrer at room temperature and stirring for 30.0 min, adjusting the rotation speed to 400 rpm.

[0018] Furthermore, in the above application, the organic pollutants include ciprofloxacin, tetracycline and methylene blue.

[0019] Furthermore, in the above-mentioned application, the iron-cobalt layered double metal hydroxide modified kaolin adsorption material that is saturated with the adsorption of organic pollutants can be recycled after microwave regeneration, and the method is as follows: after drying the iron-cobalt layered double metal hydroxide modified kaolin adsorption material that is saturated with the adsorption of organic pollutants, placing it in a microwave reactor, adjusting the power and irradiation time of the microwave reactor, starting the microwave reactor, cooling and grinding the iron-cobalt layered double metal hydroxide modified kaolin adsorption material after microwave irradiation, and obtaining the microwave-regenerated iron-cobalt layered double metal hydroxide modified kaolin adsorption material.

[0020] Preferably, the power of the microwave reactor is 800W.

[0021] Preferably, the irradiation time is 4.0 min.

[0022] The microwave regenerated iron-cobalt layered double metal hydroxide modified kaolin adsorption material obtained by the microwave regeneration method is used again in adsorbing organic pollutants in wastewater.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention adopts a hydrothermal method to modify kaolin with layered double metal hydroxides. The layered double metal hydroxides will be embedded and combined with kaolin to form a loose flower-like aggregate structure, which is conducive to the closer combination of Fe, Co, -OH and -C=O in the iron-cobalt double metal hydroxide with the -OH, -Si=O and -Al=O functional groups in kaolin, forming a stronger chemical bond, and enhancing the number and bonding strength of coordination bonds and hydrogen bonds. It effectively improves the pore structure of the original adsorption material, increases the specific surface area, provides more adsorption sites, and greatly improves the adsorption performance of the original adsorption material.

[0025] 2. The iron-cobalt layered double metal hydroxide modified kaolin prepared by the present invention is advantageous for treating ciprofloxacin solutions with a pH of 3.0 to 7.0, but disadvantageous for treating ciprofloxacin solutions with a pH greater than 7.0.

[0026] 3. The iron-cobalt layered double metal hydroxide modified kaolin prepared by the present invention is beneficial for treating ciprofloxacin, tetracycline and methylene blue.

[0027] 4. The modified kaolin preparation method of the present invention is simple and has low synthesis cost. After multiple microwave regeneration treatments, it still has a high adsorption capacity, thereby reducing wastewater treatment costs, avoiding resource waste, and reducing secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the FT-IR spectrum of natural kaolin adsorption material.

[0029] Figure 2 It is the FT-IR spectrum of the iron-cobalt layered double hydroxide modified kaolin adsorption material.

[0030] Figure 3 This is the SEM image of natural kaolin adsorption material.

[0031] Figure 4 It is the SEM image of the iron-cobalt layered double hydroxide modified kaolin adsorption material. DETAILED DESCRIPTION

[0032] Example 1 Hydrothermal method Iron-cobalt layered double metal hydroxide modified kaolin adsorption material (I) Preparation method, comprising the following steps:

[0033] 1.5941g CoCl2·6H2O and 0.8920g FeCl3·6H2O were dissolved in 10.0mL deionized water, stirred continuously for 30.0min, and then 1.0g kaolin was added to the mixture, stirred continuously for 30.0min, and then 0.9329g urea was added thereto, mixed evenly, and the resulting mixture (10.0mL) was transferred to a polytetrafluoroethylene-lined autoclave, and the solvent was thermally reacted at 160°C for 12.0h. After the reaction was completed and cooled to room temperature, the suspension was taken out, washed with deionized water to neutrality after centrifugation, vacuum dried and ground to obtain the iron-cobalt layered double metal hydroxide modified kaolin adsorption material. The layered double hydroxides will be embedded in kaolin to form a loose flower-like aggregate structure, which is conducive to the closer combination of Fe, Co, -OH and -C=O in the iron-cobalt double hydroxide and the -OH, -Si=O and -Al=O functional groups in kaolin, forming stronger chemical bonds and enhancing the number and bonding strength of coordination bonds and hydrogen bonds.

[0034] (II) Characterization

[0035] 1. Figure 1 This is the FT-IR spectrum of kaolin adsorption material. Figure 1 It can be seen that in the infrared spectrum of kaolin, the -1 and 1628cm -1 The absorption peaks at 1097cm are the stretching vibration and bending vibration of the adsorbed water OH on the surface and between the layers of the material. -1 The absorption peak nearby is the stretching vibration of Si-O in kaolin, 829 cm -1 The absorption peak nearby is the OH stretching vibration of kaolin, 736 cm -1 、565cm -1 and 468cm -1 The absorption peaks nearby represent the Si-O bending vibration, the Si-O-Al bending vibration in the vermiculite structure, and the Si-O-Si bending vibration, respectively.

[0036] 2. Figure 2 This is the FT-IR spectrum of the iron-cobalt layered double hydroxide modified kaolin adsorption material. Figure 2 It can be seen that in the infrared spectrum of kaolin modified by Fe-Co layered double hydroxide, the -1 and 1627cm -1 The absorption peaks at 1361cm -1 The absorption peak is the stretching vibration of C=O, 1022cm -1 The absorption peak near this is the stretching vibration of Si-O in kaolin, 823 cm -1The absorption peak nearby is the OH stretching vibration of kaolin, 685cm -1 and 457cm -1 The absorption peak near is the bending vibration of R-OH (R is Fe, Co), 565cm -1 The absorption peaks nearby represent the bending vibration of Si-O-Al in the vermiculite structure.

[0037] 3. Figure 3 This is a SEM image of kaolin adsorption material. The SEM image of kaolin shows that a large number of flaky structures of different sizes are accumulated in kaolin, and the interlayer spacing is relatively large and the arrangement is irregular.

[0038] 4. Figure 4 This is a SEM image of the iron-cobalt layered double hydroxide modified kaolin adsorption material. The image shows that the iron-cobalt layered double hydroxide is embedded in kaolin to form a large number of orderly flower-like structures.

[0039] Example 2 Application of Iron-Cobalt Layered Double Metal Hydroxide Modified Kaolin Adsorption Material in Adsorption of Organic Pollutants in Wastewater

[0040] The method for adsorbing organic pollutant wastewater by using iron-cobalt layered double metal hydroxide modified kaolin adsorption material is as follows: adding iron-cobalt layered double metal hydroxide modified kaolin adsorption material to wastewater containing ciprofloxacin, placing it on a magnetic stirrer for stirring for 30.0 minutes at room temperature, and adjusting the speed to 400 rpm. The absorbance of ciprofloxacin is measured at 278 nm, and the adsorption rate of ciprofloxacin by the iron-cobalt layered double metal hydroxide modified kaolin adsorption material is calculated.

[0041] Q = (C0-C e ) / C0×100% (1)

[0042] Where, Q: adsorption rate, %;

[0043] C0: initial concentration of ciprofloxacin in the reaction system, mg / L;

[0044] C e : Concentration of ciprofloxacin in the filtrate after adsorption equilibrium, mg / L.

[0045] (I) Comparison of adsorption properties of kaolin and iron-cobalt layered double hydroxide modified kaolin

[0046] Adsorption method: According to the dosage of 1.0 g / L, 0.02 g of kaolin and the iron-cobalt layered double hydroxide modified kaolin adsorbent prepared above were weighed and placed in two 50.0 mL conical flasks, and 20.0 mL of ciprofloxacin solution with an initial concentration of 20 mg / L was transferred. The rotor was placed in the conical flask and placed on a magnetic stirrer, and the speed was adjusted to 400 r / min. After reacting for 30.0 min, the mixed solution was centrifuged at 3000 rpm for 10.0 min, the supernatant was collected, filtered through a 0.45 μm filter membrane, and the absorbance of ciprofloxacin was measured at 278 nm. The adsorption rate (Q0) of the adsorbent material for ciprofloxacin was calculated according to formula (1).

[0047] Table 1 Adsorption rate of ciprofloxacin by kaolin and iron-cobalt layered double hydroxide modified kaolin adsorption materials

[0048]

[0049] As shown in Table 1, the adsorption rate of ciprofloxacin by kaolin is 34.89%, while the adsorption rate of ciprofloxacin by the iron-cobalt layered double hydroxide modified kaolin adsorption material is 97.92%, and the specific surface area of ​​kaolin is 8.65 m 2 / g, the total void volume is 0.034cm 3 / g, the specific surface area of ​​kaolin modified by iron-cobalt layered double hydroxide is 87.83m 2 / g, the total void volume is 0.268cm 3 / g, which shows that the adsorption capacity of the modified kaolin is greatly improved. This is because the adsorption process of ciprofloxacin by kaolin modified by iron-cobalt layered double hydroxide is mainly chemical adsorption, and there are also adsorption mechanisms such as van der Waals force, hydrogen bond, electrostatic interaction, and ion exchange.

[0050] (II) Effect of different pH on adsorption of organic pollutants in wastewater

[0051] Adsorption method: According to the dosage of 1.0 g / L, 0.02 g of iron-cobalt layered double hydroxide modified kaolin adsorbent material was weighed and placed in five 50.0 mL conical flasks, and 20 mL of ciprofloxacin (CIP) solution with a mass concentration of 20 mg / L and pH of 3.0, 5.0, 7.0, 9.0 and 11.0 was transferred. The rotor was placed in the conical flask and placed on a magnetic stirrer. The speed was adjusted to 400 r / min. After reacting for 30.0 min, the mixed solution was centrifuged at 3000 rpm for 10.0 min, the supernatant was collected, and filtered through a 0.45 μm filter membrane. The absorbance of ciprofloxacin was measured at 278 nm, and the adsorption rate (Q0) of the adsorbent material on ciprofloxacin was calculated according to formula (1).

[0052] Table 2 Effects of pH of Different Ciprofloxacin Solutions on the Adsorption Rate of Iron-Cobalt Layered Double Hydroxide-Modified Kaolin Adsorbent

[0053]

[0054] As can be seen from Table 2, as the solution pH increases from 3.0 to 11.0, the adsorption rate of iron-cobalt layered double hydroxide-modified kaolin adsorbent for ciprofloxacin first increases and then decreases. This is because pH affects the surface charge of the modified kaolin and the ionic species of CIP. CIP is a polar pollutant with amphoteric charges. When the solution pH < 6.1, CIP is cationic; when 6.1 < pH < 8.7, CIP is zwitterionic; when the solution pH > 8.7, the solution is anionic. In addition, the modified kaolin is negatively charged when pH > 3.0. Therefore, when 3.0 < pH < 6.1, there is electrostatic attraction between the modified kaolin and CIP. Among them, part of the adsorption also comes from the coordination of metal ions on the modified kaolin with functional groups (-C=O, -OH, and -NH2) on CIP. When pH > 8.7, there is electrostatic repulsion between the modified kaolin and the CIP solution, resulting in a decrease in the adsorption rate.

[0055] (III) Adsorption Rates of Iron-Cobalt Layered Double Hydroxide-Modified Kaolin Adsorbent for Different Pollutants

[0056] Adsorption method: Weigh 0.02 g of iron-cobalt layered double hydroxide-modified kaolin adsorbent into four 50 mL conical flasks according to the dosage of 1.0 g / L, and transfer 20 mL of ciprofloxacin, tetracycline, and methylene blue solutions with a mass concentration of 20 mg / L respectively. Place the rotor into the conical flask, place it on a magnetic stirrer, adjust the rotation speed to 400 r / min, after reacting for 30.0 min, centrifuge the mixed solution at 3000 rpm for 10.0 min, collect the supernatant, and filter it through a 0.45 μm filter membrane. Measure the absorbance of ciprofloxacin, tetracycline, and methylene blue respectively, and calculate the adsorption rate (Q0) of the adsorbent for ciprofloxacin, tetracycline, and methylene blue respectively.

[0057] Table 3 Adsorption Rates of Iron-Cobalt Layered Double Hydroxide-Modified Kaolin Adsorbent for Different Pollutants

[0058]

[0059] As can be seen from Table 3, the adsorption rates of the modified kaolin for ciprofloxacin, tetracycline, and methylene blue are all relatively high. This is because the iron-cobalt layered double hydroxide-modified kaolin adsorbent can form relatively stable complexes when adsorbing ciprofloxacin, tetracycline, and methylene blue.

[0060] (IV) Effect of regeneration cycle number on the regeneration rate of Fe-Co layered double hydroxide modified kaolin adsorption material

[0061] 1) Microwave regeneration: The saturated ciprofloxacin iron-cobalt layered double hydroxide modified kaolin adsorbent material was dried at 60° C. to constant weight, and the above materials were placed in crucibles respectively, and the crucibles were placed in a microwave oven for microwave irradiation. The microwave irradiation time was adjusted to 4.0 min, and the microwave power was set to 800 W. After the reaction was completed, the microwave equipment was turned off, cooled, and ground to obtain microwave-regenerated adsorbent materials.

[0062] 2) Adsorption of ciprofloxacin wastewater by regenerated material: The microwave-regenerated adsorption material was ground, and the above-mentioned adsorption method was repeated to adsorb the ciprofloxacin solution with an initial concentration of 20 mg / L again. The absorbance of the remaining ciprofloxacin in the filtrate was measured by UV-visible spectrophotometer, and the concentration of the remaining ciprofloxacin in the filtrate was calculated according to the standard curve, thereby calculating the adsorption rate (Q1) of ciprofloxacin by the microwave-regenerated adsorption material after regeneration.

[0063] Repeat steps 1) and 2) to obtain the second, third, fourth and fifth microwave-regenerated iron-cobalt layered double hydroxide modified kaolin adsorbent material and the regenerated adsorbent material's adsorption rates of ciprofloxacin after regeneration (Q2, Q3, Q4, Q5). The results are shown in Table 4.

[0064] First regeneration rate (%) = Q1 / Q0×100%

[0065] Second regeneration rate (%) = Q2 / Q0×100%

[0066] The third regeneration rate (%) = Q3 / Q0×100%

[0067] The fourth regeneration rate (%) = Q4 / Q0×100%

[0068] The fifth regeneration rate (%) = Q5 / Q0×100%

[0069] Table 4 Effect of regeneration times on the regeneration rate of iron-cobalt layered double hydroxide modified kaolin

[0070]

[0071] As can be seen from Table 4, with the increase in the number of cycles, the adsorption rate and regeneration rate both decreased slightly, which may be due to the fact that some active sites on the adsorbent surface are unavailable after multiple cycles. However, after five cycles, the adsorption rate can still reach more than 81%, and the regeneration rate still reaches 83%. This shows that the adsorbent still maintains good adsorption capacity and microwave regeneration ability.

Claims

1. An iron-cobalt layered double metal hydroxide modified kaolin adsorption material, characterized in that: The chemical formula of the iron-cobalt layered double hydroxide modified kaolin adsorption material is [Co 0.67 Fe 0.33 (OH)2] 0.33 (CO3) 0.16 mH2O@Al2[(OH)4 / Si2O5], with an embedded flower-like structure and a specific surface area of ​​85-90m 2 / g, the total void volume is 0.2-0.3cm 2 / g.

2. The method for preparing the iron-cobalt layered double hydroxide modified kaolin adsorption material according to claim 1, characterized in that: The method comprises the following steps: first dissolving CoCl2·6H2O and FeCl3·6H2O in deionized water, stirring continuously for 30.0 minutes to obtain a uniformly mixed mixed solution; adding kaolin to the mixed solution, stirring continuously for 30.0 minutes, and then adding urea thereto, mixing uniformly, transferring the obtained mixture to an autoclave lined with polytetrafluoroethylene for hydrothermal reaction, washing the obtained sample with deionized water to neutrality after the reaction is completed and cooled to room temperature, vacuum drying and fully grinding to obtain an iron-cobalt layered double metal hydroxide modified kaolin adsorption material.

3. The preparation method according to claim 2, characterized in that: FeCl3·6H2O and CoCl2·6H2O are based on Fe 3+ / Co 2+ The molar ratio was 1:2, and the total concentration was 1.0 M dissolved in deionized water.

4. The preparation method according to claim 2, characterized in that: The solid-to-liquid ratio of kaolin to the mixed solution is 0.1 g / 1 mL.

5. The preparation method according to claim 2, characterized in that: After adding urea, the solution pH was adjusted to 10.

0.

6. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 160° C., and the time of the hydrothermal reaction is 12.0 h.

7. Use of the iron-cobalt layered double hydroxide modified kaolin adsorption material according to any one of claims 1 to 6 in removing organic pollutants from wastewater.

8. The use according to claim 7, characterized in that: The method is as follows: add iron-cobalt layered double hydroxide modified kaolin adsorption material to wastewater containing organic pollutants and adsorb for 30.0 minutes at room temperature.

9. The use according to claim 7, characterized in that: The organic pollutants include ciprofloxacin, tetracycline and methylene blue.

10. The use according to claim 8, characterized in that: The initial concentration of the organic pollutants in the wastewater is 20 mg / L.